Optimization of solar hybrid gravity system with battery energy storage for elevation systems - Ismail, Mohd Ridhuan; Abdul Majid, Zafri Azran; Ihsan, Sany Izan; Mohd Azmi, Mohd Syahriman; Sopian, Kamaruzzaman; Abdul Aziz Moria, Hazim (UPSI Press, 2024)
This research studies the performance and efficiency of a solar hybrid gravity system integrated with battery energy storage. The study aims to optimize the design using a 50-Watt Solar PV, an 18Ah SLA Battery, and a Water Gravity Energy Storage Tank. Energy consumption was evaluated using the SLA Battery, Solar PV, and a 22-Watt Water Pump at various tank heights to measure efficiency improvements and battery lifespan extension. The methodology involved three procedures with five data loggers: a flow meter, a pyranometer, and three unit Watt Meter. Initially, a fully charged SLA Battery was tested at different tank heights (1.5m to 3.5m) every 15 minutes. Subsequently, the 50-Watt Solar PV was tested directly at a 3-meter height. Lastly, the Solar Hybrid Gravity System with Battery Energy Storage was monitored for seven days at a 3-meter height. Results indicated a 600% increase in battery performance at 80% Depth of Discharge (DOD), suggesting the battery's optimal use as a backup power source, thereby extending its lifespan. The SLA Battery shows a 22.1% charging and discharging loss at 5% DOD, while the 22-Watt Water Pump is achieved an 11.0 L/min rate at peak solar radiation, with a maximum motor power of 24.32 Watts. The minimum solar radiation required for efficient pump operation was 300 W/m². In conclusion, the study optimizes the solar hybrid gravity system's energy efficiency, reduces battery dependence, and enhances battery lifespan, promoting sustainable solutions for elevation applications.